Non-Conditioned, Unconscious Intra-Individual Variation - Gotzon Aurrekoetxea (Languages)
Far from the uniformity of language and the ideal speaker, it is assumed that language varies even within the same speaker, and that such variation is intrinsic to this speaker. This intra-individual variation has been understood mostly as stylistic variation (Hernández-Campoy & Cutillas-Espinosa, 2012) and is becoming increasingly important (Werth et al., 2021) in the scholarly literature. Admitting that stylistic variation exists, I argue that not all intra-individual variation is conditioned and conscious, according to my data. The analysis will be carried out with data from the Basque linguistic atlas (EHHA) (Aurrekoetxea & Videgain, 2010–2020), which examines systematically the intra-individual variation of speakers in the elicitation phase. Based on these data, the aim of this paper is to show that there are also non-conditioned and unconscious types of variation, and to give a preliminary outline of a theory that accommodates these types of variation.